Emblematic codeswitching represented in fiction: The case of the Malay discourse markers lah, what, ah - Jaafar, Mohammad Fadzeli Bin (Journal of Modern Languages, 1999)
In this study, I will discuss the usage and functions of -lah in written discourse. For this purpose I have chosen a short passage from a short story written by Siew Yue Killingley.’ It is the assumption of this study that -lah carries several different functions, such as softening, confirming, emphasising, parsing, intensifying, and expressing.